Enhanced Effective Connectivity From Ipsilesional to Contralesional M1 in Well-Recovered Subcortical Stroke Patients - Peng, Yanmin; Liu, Jingchun; Hua, Minghui; Liang, Meng; Yu, Chunshui (Frontiers in Neurology, 2019)
Background and Purpose—Interhemispheric imbalance may provide a framework for developing new strategies to facilitate post-stroke motor recovery especially for patients in chronic stage. Using effective connectivity analysis, we aimed to investigate interactions between the bilateral primary motor cortices (M1) and their correlations with motor recovery and M1-related structural and functional changes in well-recovered patients with chronic subcortical ischemic stroke. Methods—Twenty subcortical stroke patients and 20 normal controls underwent multimodal magnetic resonance imaging (MRI) examinations. During the movement of the affected hand, functional MRI was used to calculate the M1 activation and M1-M1 effective connectivity. Diffusion tensor imaging was used to compute the fractional anisotropy (FA) of the affected corticospinal tract (CST) and M1-M1 anatomical connection. After intergroup comparisons, the altered M1-M1 effective connectivity was correlated with the motor recovery, M1 activation and FA of the affected CST and M1-M1 anatomical connection in patients. Results—Compared to normal controls, stroke patients exhibited increased excitatory effective connectivity from ipsilesional to contralesional M1 and increased ipsilesional M1 activation, however, they showed reduced FA values in the affected CST and M1-M1 anatomical connection. The increased effective connectivity was positively correlated with motor score and the FA of the M1-M1 anatomical connection, but not with the M1 activation and the FA of the affected CST in these patients. Conclusions—These findings suggest that the enhanced M1-M1 effective connectivity from ipsilesional to contralesional hemisphere plays a supportive role in motor recovery in chronic subcortical stroke, but its enhancement depends on the integrity of the underlying M1-M1 anatomical connection.